Desenvolvimento de um equipamento computadorizado de movimentação passiva contínua para cotovelo e antebraço - Callegaro, Aline Marian (2010)
This research demonstrates the development of a new principle of operation for elbow and forearm continuous passive motion (CPM) equipment. For that were integrated knowledges of Physical Therapy and Production Engineering to make a prototype of a CPM device for the purpose of enabling the programming of various sequences of passive movements of elbow and forearm by means of computerized numerical control (CNC). The conceptual design of prototype mechanical equipment was carried out, as well as the construction and development of a program to specify the principles of operation of the equipment. Computerized CPM allows the independent or synchronized passive movements on two axes: elbow flexion/extension and forearm pronation/supination. The prototype has stepper motors connected to a microcomputer by means of drivers. The motors are controlled by commercial CNC machine software control. The language read and interpreted by this program is generated by other software, this was developed for this equipment to facilitate its use by the Physical Therapists. It has language accessible to this professionals and it allows the insertion of such variables as time and angle. The software calculates the speed of movement with these variables automatically. Data entered into the program are saved and generate a text file with standard CNC language, which is recognized by the program control. The sequences of movements are created by Physical Therapist and adapted to patients according to treatment goals and the individual characteristics. The control software also provides the flexion/extension and pronation/supination range of motion (ROM) passive evaluation, the data of each patient can be stored for monitoring progress and possible reuse. Based on what was done, we can assert that this operating principle can be used in CPM device, the software developed can be used on any machine of this type wich CNC principle of operation and if them have the availability of two axes of movement. This technique can be used to other equipments specific to the health area.